TRANSFORMATION OF STRATEGIC HUMAN RESOURCE SOLUTION IN THE PORT OPERATOR CORPORATION : A SCENARIO APPROACH - Giswari Meisya Nabilah; Yos Sunitiyoso (RADJA PUBLIKA, 2026)
This research existed as conducted to assess the compatibility of scenario planning to prepare plausible strategies for learning and consulting company that functions as part of an SOE port operator group, in developing its capabilities to meet the difficulties of fulfilling the parent company's mandate as an HR solution enabler. A qualitative research initiated by combine external environmental analysis using PESTEL and internal resource evaluation with the VRIO model to identify critical uncertainties that impact the company's strategic direction. These variables form the basis of a four-scenario matrix that captures a range of believable upcoming conditions. Each circumstance exists as advanced with detailed stories, calculated consequences, promptly warning signals, and reply possibilities. From the more extensive set of driving influences, two vital ambiguities stand as determined: the degree of calculated freedom granted to the corporation within the SOE group and the level of marketplace openness beyond the inside harbor operator ecosystem. The discoveries indicating that (1) advancement focuses vary notably between contexts but still demand a baseline, especially in terms of resource oversight capacities, strategy standardization, and business abilities; (2) Excessive dependency on third-party ability without a systematic inner competency roadmap poses long-term calculated risks; and (3) Gradual skill advancement, aligned with feasible upcoming conditions, empowers bodies to balance short-term efficiency necessities and performance targets with long-term calculated placement. The investigation concludes that context organization plays a essential position as a business approach tool while as well highlighting the importance of ordered skill construction that aligned with organization long-term tactical intent and institutional oversight restrictions.